Effect of surfactants on phase, crystal growth and photocatalysis of calcium stannate synthesized by cyclic microwave and calcination combination - Patcharanan Junploy (2018)
© 2018 Springer Science+Business Media B.V., part of Springer Nature Calcium stannate (CaSnO3) was successfully synthesized in the solutions containing different surfactants by cyclic microwave and calcination combination. Phase, morphology and vibration mode were characterized by X-ray diffraction, field emission scanning electron microscopy and Fourier transform infrared spectroscopy. Growth mechanism of the products was also explained according to the analytical results. Their photocatalytic activities were tested through methylene blue (MB) degradation induced by UV radiation. In the MB solution with pH 6, the S-CTAB product showed the highest decolorization efficiency of 89.1% and the highest rate constant of 4.374 × 10−3min−1.